Предмет: Математика,
автор: arina6868
помоги пожалуйста да
Приложения:
Ответы
Автор ответа:
0
а) 2b/4a^2
б) 9(а-3)(а+3)/3(а+3)=3а -9
б) 9(а-3)(а+3)/3(а+3)=3а -9
Автор ответа:
0
Пошаговое объяснение:
а)
6а²b³/8a⁴b² = 3a²b³/4a⁴b² = 3b/4a²
б)
9а² - 81/3а + 9 = 9(а - 3)*(а + 3) / 3(а + 3) =
9(а - 3)/3 = 3(а-3)/1 = 3(а - 3) = 3а - 9
Похожие вопросы
Предмет: Физкультура и спорт,
автор: Аноним
Предмет: Английский язык,
автор: gajdajsasa2
Предмет: Английский язык,
автор: mogilnitcka
Предмет: Математика,
автор: arsenijsafonov55
Предмет: Русский язык,
автор: stttt2019